Efektifitas Pemberian Exercise dan Tens dalam Penurunan Nyeri pada Pasien HNP di Praktik Mandiri FisioterapiAnugerah Sehat Tahun 2022 - Santo Damerius Silitonga (Yayasan Literasi Sains Indonesia, 2022)
Low back pain can be influenced by several risk factors, including age, gender, body mass index, type of work that is usually associated with certain postures (sitting, standing, lifting, pushing, bending) and years of service. The purpose of the study was to determine the effectiveness of giving exercise and TENS in reducing pain in patients with HNP in the Independent Practice of Physiotherapy Anugerah Sehat in 2022. The type of research used was a quantitative research type, with the research design used was a quasi-experimental approach with a pre-test and post-test two groups. . This research will be conducted at Anugerah Sehat Physiotherapy Independent Practice in May-June 2022. The population in this study was 40 HNP patients. The sampling technique in this research is Total Sampling. Bivariate data analysis used Paired Sample T Test analysis. The descriptive summary results from the data before and after exercise and TENS that the mean value before exercise and TENS is 5.6364, then the mean value after exercise and TENS is 2.0000. Results sig. 0.000 <0.05, so it was concluded that there was a significant difference in the pain of HNP patients before and after exercise and TENS.